Inhibition of astrocyte signaling leads to sex-specific changes in microglia phenotypes in a diet-based model of cerebral small vessel disease - Jenna L. Gollihue; Khine Zin Aung; Colin B. Rogers; Leopoldine B. Galopin; Nicholas A. Wright; Pradoldej Sompol; Erica M. Weekman; Yuriko Katsumata; Josh M. Morganti; Christopher M. Norris (Journal of Neuroinflammation)
Abstract Hyperhomocysteinemia (HHcy)-inducing diets recapitulate cerebral small vessel disease phenotypes in mice including cerebrovascular pathology/dysfunction, neuroinflammation, synaptic deficits, and cognitive decline. We recently showed that astrocyte signaling through calcineurin(CN)/nuclear factor of activated T cells (NFATs) plays a causative role in these phenotypes. Here, we assessed the impact of astrocytic signaling on microglia, which set the inflammatory tone in brain. Seven-to-eight-week-old male and female C57BL/6 J mice received intrahippocampal injections of adeno-associated virus (AAV) expressing EGFP (AAV2/5-Gfa2-EGFP) or AAV expressing the NFAT inhibitor VIVIT (i.e., AAV2/5-Gfa2-VIVIT-EGFP). Mice were then fed with control chow (CT) or B-vitamin-deficient chow for 12 weeks to induce HHcy. Immunohistochemistry and Western blot analyses suggested that expression of the homeostatic microglial marker, P2RY12, responded differently to AAV treatments depending on diet and sex. We next conducted single-cell RNA sequencing (scRNA-seq) to determine if microglial genes and/or clustering patterns were differentially sensitive to diet and AAV, depending on sex. In males, disease-associated microglial genes and subclusters were overrepresented in HHcy-treated mice, while VIVIT promoted the appearance of homeostatic microglial genes and clusters. In contrast, microglial genes in females were less sensitive to diet and AAV treatments, though disease-like patterns were also observed in the HHcy condition. Very few of the HHcy-sensitive microglial genes in females were affected by VIVIT. Though based on small sample sizes, the results suggest a sexually dimorphic influence of astrocyte signaling on microglial transcriptional phenotypes in the context of HHcy and small cerebral vessel disease. However, these interpretations will need to be bolstered with additional biological replicates and more stringent statistical analyses.